Responsibility in Marriage of Persons With Mental Disabilities Reviewed Based on Law Number 16 of 2019 Concerning Marriage and Law Number 8 Of 2016 Regarding Persons With Disabilities (Case Study In Selapajang Village, Cisoka District, Tangerang District) - Badriah, Nurliatul; Tahir, Palmawati; Itang, Itang (Jurnal Hukum Replik, 2024)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on Belief in One Almighty God. In running a household, both a husband and a wife must carry out their respective obligations as a husband and wife in accordance with Article 34 of Law Number 16 of 2019 concerning Marriage. In practice, there is a marriage, where a wife has a disability. The wife who has a disability cannot carry out her obligations as a wife in accordance with Article 34 paragraph (2) which states that the wife is obliged to manage the household as well as possible. Therefore, it is necessary to study the responsibilities for rights and obligations in marriages for people with mental disabilities in Selapajang Village, Cisoka, Tangerang, is the marriage in accordance with Law Number 16 of 2019 concerning Marriage and Law Number 8 of 2016 concerning Persons with Disabilities. The research method used in writing this thesis is a qualitative method with a typologyEmpirical legal research is here as the main research type, while normative legal research is a supporting research type.The data source used is secondary data with data collection techniques, namely the study of documents or library materials. The results showed that The marriage that is pursued is in line with Article 34 paragraph (1), where the husband has carried out his duties and obligations mentioned in Article 34 paragraph (1). In addition, the research also shows that marriage is not in line with Article 34 paragraph (2), where a wife who has a mental disability cannot carry out her obligations as a wife mentioned in Article 34 paragraph (2).Keywords: Responsibility, Marriage, People with Mental Disabilities